Influence of type 2 diabetes microangiopathy on bone mineral density and bone metabolism: A meta-analysis. Issue 10 (October 2022) - Zhao, Jinlong; Liang, Guihong; Luo, Miaohui; Yang, Weiyi; Xu, Nanjun; Luo, Minghui; Pan, Jianke; Liu, Jun; Zeng, Lingfeng
Abstract: Background: Diabetic microangiopathy is a type of vascular dysfunction. The effect of type 2 diabetes microangiopathy (DMA) on bone mineral density (BMD) and bone metabolism is still unclear. Objective: A meta-analysis was performed to investigate the effects of microangiopathy on BMD and bone metabolism in type 2 diabetic patients. Methods: We searched the PubMed, Embase, Cochrane Library and CNKI databases to identify observational studies investigating the effects of type 2 diabetes microangiopathy on BMD or bone metabolism. The time limit for the literature retrieval was from the establishment of the database to September 25, 2021. The Newcastle–Ottawa scale (NOS) and the Agency for Healthcare Research and Quality (AHRQ) scale were used to evaluate the quality of the studies. RevMan 5.3 software was used for the data analysis. Stata 14.0 was used to quantitatively evaluate the publication bias of the outcome indicators. Results: In total, 12 observational studies were included, including 7 cohort studies, 4 case–control studies and 1 cross-sectional study. In total, 2, 500 patients with type 2 diabetes were included. Among them, 1, 249 patients had microangiopathy (DMA group), and 1, 251 patients did not have microangiopathy (control group). The results of the meta-analysis showed that the BMDs of the femoral neck (SMD = −1.34, 95% CI = −2.22 to −0.45, P = 0.003), lumbar spine (SMD = −0.69, 95% CI = −1.31 to −0.08, P = 0.03) and Ward's triangle (SMD = −2.84, 95% CI = −4.84 to −0.83, P = 0.006) in the DMA group were lower than those in the control group. In the comparison of the bone metabolism indexes, the contents of N-terminal propeptide of type I procollagen (P1NP) (SMD = 0.18, 95% CI = 0.03 to 0.32, P = 0.02), osteocalcin (SMD = 6.97, 95% CI = 3.46 to 10.48, P < 0. 0001), parathyroid hormone (PTH) (SMD = 0.38, 95% CI = 0.03 to 0.73, P = 0.03) and C-telopeptide of type 1 collagen (CTX) (SMD = 0.39, 95% CI = 0.03 to 0.75, P = 0.03) in serum from the DMA group were higher than those in serum from the control group. The serum content of 25-hydroxyvitamin D3 (25(OH)D3 ) (SMD = −0.63, 95% CI = −1.19 to −0.07, P = 0.03) in the DMA group was lower than that in the control group. There was no significant difference in serum alkaline phosphatase (ALP), calcium or phosphorus between the two groups (P > 0.05). Conclusions: Type 2 diabetes microangiopathy can reduce the lumbar spine, femoral neck and Ward's triangle BMD and has a higher risk of osteoporosis or osteoporosis fractures. The levels of P1NP, PTH, CTX and OC in the serum of patients with type 2 diabetes microangiopathy are higher, and the lower 25(OH)D3 content may be a mechanism by which DMA destroys bone metabolism balance. Highlights: The effect of type 2 diabetes microangiopathy on bone mineral density and bone metabolism is still unclear. Type 2 diabetes microangiopathy can reduce the lumbar spine, femoral neck and Ward's triangle BMD. Type 2 diabetes microangiopathy has a higher risk of osteoporosis or osteoporosis fractures.